Walkability Explorer. An Evaluation and Design Support Tool for Walkability - Blečić, Ivan; Cecchini, Arnaldo; Congiu, Tanja; Fancello, Giovanna; Trunfio, Giuseppe Andrea (TeMA - Journal of Land Use, Mobility and Environment, 2014)
Walkability Explorer is a software tool for the evaluation of urban walkability which, we argue, is an important aspect of the quality of life in cities. Many conventional approaches to the assessment of quality of life measure the distribution, density and distances of different opportunities in space. But distance is not all there is. To reason in terms of urban capabilities of people we should also take into account the quality of pedestrian accessibility and of urban opportunities offered by the city. The software tool we present in this paper is an user-friendly implementation of such an evaluation approach to walkability. It includes several GIS and analysis features, and is interoperable with other standard GIS and data-analysis tools.